Upaya Meningkatkan Kemampuan Menulis Teks Eksposisi dan Prestasi Belajar Bahasa Indonesia dengan Metode Inkuiri di Kelas X-1 Semester Ganjil SMA Kristen 1 Metro - Emilda, Mardian (STKIP PGRI Bandar Lampung, 2023)
This study aims to improve the ability to write exposition texts and Indonesian language learning achievement in class X IPA 1 using the inquiry method. The formulation of the problem is how far the ability to write exposition texts and the Indonesian language learning achievement of Science class X.1 of Christian High School 1 Metro improves. Research methods and data collection tools using test techniques and non-test techniques. Results and discussion on pre-cycle 24.29%, cycle I to 52.98%, or an increase of 28.69%. In cycle II it got 61.63% and cycle III increased to 81.18%, there was an increase of 19.48%. While the average Pre-cycle learning achievement reached 61.11, the first cycle increased to 76.29, an increase of 18.11%. Cycle II got an average of 83.33, in cycle III it became 90, or an increase of 6.67%. The pre-cycle learning completeness was 14.81%, the first cycle was 59.25%, the second cycle was 77.77% and the third cycle was 100%.